Analisis Beban Kerja dan Kepuasan Kerja terhadap Turnover Intention Karyawan pada Taman Safari Bali - I Gusti Ayu Mahayani; I Nyoman Suka Sanjaya; Ni Wayan Sukartini (ARZUSIN, 2025)
This study is motivated by the limited research on factors influencing turnover intention in conservation-based tourism, despite its significant impact on organizational sustainability and workforce stability. The study aims to examine the influence of workload and job satisfaction on turnover intention among employees at Taman Safari Bali. A quantitative research design was employed using purposive sampling with 85 respondents. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The results indicate that workload has a negative effect on turnover intention (β = -0.394) and a positive effect on job satisfaction (β = 0.302), while job satisfaction negatively affects turnover intention (β = -1.942); however, none of these relationships were statistically significant (p > 0.05). These findings suggest that variations in workload and job satisfaction do not significantly influence employees’ intention to leave the organization. Theoretically, this study contributes to the literature by highlighting the limited predictive power of internal variables on turnover intention within the context of conservation tourism. Practically, it offers empirical data from Bali’s tourism sector, which has been predominantly represented by hospitality-focused studies. Future research is recommended to adopt a longitudinal approach, expand regional coverage, and consider external variables such as leadership style, organizational climate, and work-life balance to achieve a more comprehensive understanding.